Problem-Based Learning-Oriented Learning Video Media Uses the Filmora Application for Science Content - Dewanti, Ida Ayu Tiara Krisna; Nice Maylani Asril (MIMBAR PGSD Undiksha, 2023)
The availability of various learning media that support science learning activities still needs to be improved. This study aims to develop PBL-oriented instructional video media using the Filmora application on animal characteristics and their habitat material. This type of research is development research using the ADDIE model. The subjects of this study were design experts, two learning content experts, and two learning media experts. The test subjects for this study included two teachers for the practitioner test, three people for the individual trial, and nine students for the small group trial. The population of this study was 20 people. The sampling technique uses Saturated sampling. Data collection methods are interviews, observations, questionnaires, and tests. The instrument collects data,  the rating scale. The data analysis techniques used in this study are descriptive qualitative analysis techniques, quantitative descriptive analysis techniques, and inferential statistical analysis. The results of the research are the results of the assessment given by subject content experts,  94.5% (very good), learning media experts,  91.81% very good), and learning design experts, 92% (very good). The results of practicality trials, according to the teacher, were 91.81% (very good), 97.3% individual trials (very good), and small group trials 97.1 (very good). The results of the t-test found that there were significant differences before and after using PBL-oriented instructional video media using the Filmora application. It was concluded that the instructional video media was effectively used in the material on the characteristics of animals and their habitat.